2005
DOI: 10.1145/1060710.1060716
|View full text |Cite
|
Sign up to set email alerts
|

Scale-free geometry in OO programs

Abstract: Though conventional OO design suggests programs should be built from many small objects, like Lego bricks, they are instead built from objects that are scale-free, like fractals, and unlike Lego bricks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
122
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(126 citation statements)
references
References 8 publications
3
122
0
1
Order By: Relevance
“…If they are constructed as directed graphs, the degree distributions of the inward and outward links differ, with the exponent for incoming edges being less than that of the outgoing and showing a better fit to the power law (Valverde & Solé 2003;Potanin et al 2005;Concas et al 2007;Louridas et al 2008). Solé & Valverde (2004) identify software networks as heterogeneous, scale-free and with some modular structure -a characterisation that also includes a wide range of biological and technical systems.…”
Section: Software As Typicalmentioning
confidence: 99%
“…If they are constructed as directed graphs, the degree distributions of the inward and outward links differ, with the exponent for incoming edges being less than that of the outgoing and showing a better fit to the power law (Valverde & Solé 2003;Potanin et al 2005;Concas et al 2007;Louridas et al 2008). Solé & Valverde (2004) identify software networks as heterogeneous, scale-free and with some modular structure -a characterisation that also includes a wide range of biological and technical systems.…”
Section: Software As Typicalmentioning
confidence: 99%
“…Both automata exhibit some typical graph properties that we find in real-world software systems. First, software is not made of "Lego blocks" [20]. The topology of both automata varies greatly.…”
Section: Structural Analysismentioning
confidence: 99%
“…Prior analysis of static class collaboration networks [40,44] suggest an anti-correlation, characterizing some functions as source or sinks. We found no significant correlation between in and outdegree of functions in the disassembled executables (Fig.…”
Section: Correlationsmentioning
confidence: 99%
“…Focusing on the properties of directed graphs, Potanin et al [44] examined the binary heap during execution and took a snapshot of 60 graphs from 35 programs written in Java, Self, C++ and Lisp. They concluded that the distributions of incoming and outgoing object references followed a power law with α in ≈ 2.5 and α out ≈ 3.…”
Section: (F)mentioning
confidence: 99%